2020
DOI: 10.1155/2020/8837024
|View full text |Cite
|
Sign up to set email alerts
|

Stress Reactivity Influences the Relationship between Emotional Labor Strategies and Job Burnouts among Chinese Hospital Nurses

Abstract: Extant studies mostly focused on the buffering role of social and external organizational resources and personal mental resources. However, there is no research exploring the moderating role of personal physiological resources (e.g., stress reactivity). The present study is aimed at examining the interactive effect of emotional labor and stress reactivity on job burnout. The present study utilized cortisol content in a 1 cm hair segment as the biomarker of total stress reactivity in one month. The participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…These results extended the interaction pattern between job resources and work environments from the traditional perspective of the diathesis stress model to the novel perspectives of the differential susceptibility model and the vantage sensitivity model when the focus was expanded from the adverse and pathogenic responses in adverse environments to the adaptive responses in supportive environments. These results also provided another evidence for the extension of the JDR model to personal biological resources from social and organizational resources and personal mental resources, together with a recent finding that the interaction patterns between stress reactivity and emotional labor might follow the differential susceptibility model or the vantage sensitivity model (Deng et al, 2020).…”
Section: Discussionsupporting
confidence: 62%
See 4 more Smart Citations
“…These results extended the interaction pattern between job resources and work environments from the traditional perspective of the diathesis stress model to the novel perspectives of the differential susceptibility model and the vantage sensitivity model when the focus was expanded from the adverse and pathogenic responses in adverse environments to the adaptive responses in supportive environments. These results also provided another evidence for the extension of the JDR model to personal biological resources from social and organizational resources and personal mental resources, together with a recent finding that the interaction patterns between stress reactivity and emotional labor might follow the differential susceptibility model or the vantage sensitivity model (Deng et al, 2020).…”
Section: Discussionsupporting
confidence: 62%
“…Previous studies had demonstrated that stress reactivity could moderate the relationship between environmental factors and adolescents' psychological adaptations (Wiel et al, 2004;Obradovi et al, 2010Obradovi et al, , 2015Owens et al, 2018;Xu et al, 2019) and the relationship between emotional labor and job burnouts (Deng et al, 2020). Thus, we hypothesized that hair cortisol levels (or stress reactivity) could moderate the relationship between environmental factors and work-related outcomes among Chinese nurses.…”
Section: The Present Studymentioning
confidence: 93%
See 3 more Smart Citations